The Effect Of Service Quality On Inpatient Satisfaction At The Muara Kelingi Community Health Center In Musi Rawas District - Sudarmiyati, Sudarmiyati; Ayub, Ayub; Adhini, Septi (Journal of Multidisciplinary Research, 2025)
This study aims to determine the influence of service quality indicators, namely direct evidence, reliability, responsiveness, assurance, and empathy on inpatient satisfaction at the Regional Public Service Agency (BLUD) Technical Implementation Unit (UPT) Muara Kelingi Health Center. The research method used is a quantitative method and uses primary data through the distribution of questionnaires to inpatients at the Muara Kelingi Health Center. The sample in this study was 164 respondents with a simple random sampling technique with Likert scale measurement. Data analysis was carried out by simple linear regression, t-test, and determination coefficient using SPSS version 27. The results showed that the quality of service had a significant influence on inpatient satisfaction at the BLUD UPT Muara Kelingi Health Center, Musi Rawas Regency, with a calculated t value of 9.521 > t table 1.974 and a significance of 0.000 < 0.05 hereby declared H0 rejected and Ha accepted. The results of the determination coefficient test were found to be 0.764 R Square (R2) value, indicating that 76.4% of patient satisfaction was influenced by service quality while 23.6% was influenced by other variables that were not included in this study. To improve the level of service provided at the BLUD UPT Muara Kelingi Health Center, Musi Rawas Regency, it is necessary to make efforts to improve the quality of service so that patient satisfaction and organizational goals can be realized to the maximum.